Acute procedural efficacy and safety of a novel cryoballoon for the treatment of paroxysmal atrial fibrillation: Results from the POLAR ICE study. (23rd February 2023) - Martin, Claire A.; Tilz, Roland R. R.; Anic, Ante; Defaye, Pascal; Luik, Armin; de Asmundis, Carlo; Champ‐Rigot, Laure; Iacopino, Saverio; Sommer, Philipp; Albrecht, Elizabeth M.; Raybuck, Jonathan D.; Richards, Elizabeth; et al.
Abstract: Introduction: Pulmonary vein isolation (PVI) is well established as a primary treatment for atrial fibrillation (AF). The POLAR ICE study was designed to collect prospective real world data on the safety and effectiveness of the POLARx TM cryoballoon for PVI to treat paroxysmal AF. Methods: POLAR ICE, a prospective, non‐randomized, multicenter (international) registry (NCT04250714), enrolled 399 patients across 19 European centers. Procedural characteristics, such as time to isolation, cryoablations per pulmonary vein (PV), balloon nadir temperature, and occlusion grade were recorded. PVI was confirmed with entrance block testing. Results: Data on 372 de novo PVI procedures ( n  = 2190 ablations) were collected. Complete PVI was achieved in 96.8% of PVs. Procedure and fluoroscopy times were 68.2 ± 24.6 and 15.6 ± 9.6 min, respectively. Left atrial dwell time was 46.6 ± 18.3 min. Grade 3 or 4 occlusion was achieved in 98.2% of PVs reported and 71.2% of PVs isolation required only a single cryoablation. Of 2190 cryoapplications, 83% had a duration of at least 120 s; nadir temperature of these ablations averaged −56.3 ± 6.5°C. There were 6 phrenic nerve palsy events, 2 of which resolved within 3 months of the procedure. Conclusion: This real‐world usage data on a novel cryoballoon suggests this device is effective, safe, and relatively fast in centers with cryoballoon experience. These data are comparable to prior POLARx reports and in keeping with reported data on other cryoballoons. Future studies should examine the long‐term outcomes and the relationship between biophysical parameters and outcomes for this novel cryoballoon.